2024
DOI: 10.18502/kss.v9i14.16133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Service Quality on Purchase Decision with Customer Satisfaction and Hedonistic View as Mediating Variables

Rafael Anggoro Prayogo,
Gede Ariadi

Abstract: Practicing pilot service in a game is popular. One of them is EL’s Merchant Pilot Service. This study was conducted to find the significant impact of service quality that influenced purchase decisions with customer satisfaction and hedonistic view as mediating variables using Smart PLS 3.0 software. The sample of respondents was 150, and they were asked to grade all the indicators using a five-point Likert scale. The results showed that service quality had a significant impact on purchase decisions. The hedoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Service quality is an assessment of the suitability of the service received with the expected service (Prayogo & Ariadi, 2024). According to Kuswibowo et al, (2023), service quality is an activity, or a group of certain activities, which are usually intangible, which occur through the relationship between the service facilitator and the service user as well as the physical resources used to support the services provided by the service facilitator.…”
Section: Literature Review Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Service quality is an assessment of the suitability of the service received with the expected service (Prayogo & Ariadi, 2024). According to Kuswibowo et al, (2023), service quality is an activity, or a group of certain activities, which are usually intangible, which occur through the relationship between the service facilitator and the service user as well as the physical resources used to support the services provided by the service facilitator.…”
Section: Literature Review Service Qualitymentioning
confidence: 99%
“…Research from Prayogo & Ariadi, (2024) has stated that service quality influences purchase decisions, but customer satisfaction does not mediate the relationship between service quality and purchase decisions. However, other research has found that customer satisfaction mediates service quality in purchase decisions (Bekti Kumoro & Denpharanto Agung Krisprimandoyo, 2023).…”
Section: Figure 4 Theoretical Frameworkmentioning
confidence: 99%